From waste to value: Lapachol from teak wood waste as a green catalyst for sustainable soda cooking of Acacia and Eucalyptus - Sari, Esty Octiana; Utami, Syelvia Putri; -, Evelyn; Nakagawa-Izumi, Akiko; Ohi, Hiroshi (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2025)
The development of a sustainable catalyst as an alternative to synthetic anthraquinone (AQ) is urgently needed for a more efficient pulping process. This study investigates the potency of lapachol, a natural naphthoquinone isolated from teak (Tectona grandis) wood waste, as a catalyst in soda cooking of three industrially important hardwoods: Acacia crassicarpa, Eucalyptus pellita, and Eucalyptus globulus. Approximately 97.7% purity of lapachol was isolated and applied at 0.09% (on oven-dry wood). For comparison, the commercial synthetic additive, 2-Methylanthraquinone (2-MAQ) was also used at the same dosage. Cooking experiments were conducted at 160°C under varying alkali dosages (23, 27, 31%) and times (4, 5, 6 h). The result revealed that the delignification performance was species-dependent: A. crassicarpa (S/V=0.74) was the hardest, while E. globulus (S/V=3.04) was the easiest to delignify. Notably, E. pellita (S/V=2.04) shows the greatest selectivity index. Lapachol shows the capability of enhancing delignification across the three wood species by decreasing the residual lignin by up to 5% in A. crassicarpa, 5% in E. Pellita, and 2% in E. globulus compared with soda cooking (control). Although the delignification is slightly lower than 2-MAQ, lapachol maintains pulp yields comparable to or higher than 2-MAQ. The selectivity index analysis confirmed that lapachol improved the balance between lignin removal and carbohydrate preservation, with the benefits most pronounced in E. globulus. These findings underscore lapachol as a promising sustainable pulping catalyst, offering the potential for impactful industry transformation through sustainable innovation.